Selection of nuclear reactor and its system features for PC1 nuclear icebreaker - Lainio, Valtteri (My University, 2026)
A nuclear-powered icebreaker concept ship titled IBELO is under development at Elomatic. The ship targets to meet PC 1 ice class, requiring year-round operation in all polar waters. Nuclear power offers high power, a fuel with high energy density and reduction in the refueling time, responding well to operational requirements of the concept ship. Development of the emerging generation 4 reactors would offer beneficial features related to nuclear power implementation to commercial ships. Lack of regulatory and more practical standards are main barriers for nuclear power adaptation to commercial ship. This thesis aims to find most suitable options and solutions for concept ship machinery arrangement. Axiomatic design process is utilized to determine the suitable system features, starting from functional requirement and resulting most suitable system feature determination. Electrical propulsion system was selected because of its load following capabilities and flexibility. Converting nuclear thermal energy to electricity with turbines is considered most suitable, with turbine features for reheating and at least three pressure cylinders. Reactor validation was performed utilizing the analytical hierarchy process (AHP) method and initial screening. Validation process found Lead-cooled fast reactor (LFR) Sealer-55 with 55 MW electrical power to be the most suitable option for the concept ship.
Keywords: nuclear power; nuclear-powered ship; icebreaker; small modular reactor; Generation 4; analytical hierarchy process